Clinical Results of Surgically Treated Medial Humeral Epicondylar Apophyseal Avulsion Injury in Children and Adolescent - Joshi, Ruban Raj; Sundararaj, Gabriel David (Journal of Lumbini Medical College, 2016)
Introduction: Fractures of the medial humeral epicondyle represent approximately 10% of all paediatric elbow fractures. Objective of our study was to assess treatment outcomes of children and adolescent with medial epicondylar fracture of the elbow using standard operative protocols. Methods: 20 surgically treated fractures of the medial humeral epicondyle were analysed & reviewed for their epidemiological, clinical and surgical parameters. A valgus stress test was performed under general anesthesia or sedation. All patients underwent open reduction internal fixation using a similar technique. The medial epicondylar fragment was anatomically reduced and fixed in all cases with screws, Kirshner wires or tension band wiring. At final evaluation, union (radiologically) and elbow function [MAYO elbow performance score (MEPS)] was assessed. Results: An evaluation of all of our patients after a mean follow-up of 8.75 months (SD=4.76) after initial surgery was possible. The mean age of patients at the time of injury was 10.8 years (SD=2.3). Fifteen (75%) dominant elbows were injured in our study and 12(60%) elbows had an associated elbow dislocation. On examination in operating room post anaesthesia, all of the elbow injuries revealed some degree of valgus instability. All of our patients (n=20) showed good to excellent results in the MAYO elbow performance score (MEPS). Radiographically, union was achieved in all cases. Three patients developed postoperative ulnar nerve neuropraxia, all recovered at time of final follow up. One patient developed mild lateral heterotrophic ossification but did not require any additional surgical intervention. Conclusion: Our results suggest that open reduction internal fixation of displaced medial epicondyle fractures leads to satisfactory motion and function. A valgus stress test in operating room can reveal the true nature of joint instability that can warrant operative stabilization of medial epicondylar injuries. Journal of Lumbini Medical College. 2014;2(2):31-36.